2019
DOI: 10.1136/heartjnl-2018-314305
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcomes of unstable angina compared with non-ST-elevation myocardial infarction

Abstract: ObjectiveAssess the relative incidence and compare characteristics and outcome of unstable angina (UA) and non-ST-elevation myocardial infarction (NSTEMI).DesignTwo independent prospective multicentre diagnostic studies (Advantageous Predictors of Acute Coronary Syndromes Evaluation [APACE] and High-Sensitivity Troponin in the Evaluation of Patients With Acute Coronary Syndrome [High-STEACS]) enrolling patients with acute chest discomfort presenting to the emergency department. Central adjudication of the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 21 publications
5
33
2
2
Order By: Relevance
“…The incidence of definite UA in our (complete) cohort was 5%. This is in line with recently published results by Puelacher et al, who investigated the incidence and outcomes of UA patients compared to NSTEMI patients in 8992 patients from the international APACE study and patients from a stepped wedge cluster RCT (4739 patients) which is still ongoing (HighSTEACS) [ 10 ]. However, wide ranges of incidence rates are reported, most likely as a consequence of an absent universal definition for UA [ 7 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The incidence of definite UA in our (complete) cohort was 5%. This is in line with recently published results by Puelacher et al, who investigated the incidence and outcomes of UA patients compared to NSTEMI patients in 8992 patients from the international APACE study and patients from a stepped wedge cluster RCT (4739 patients) which is still ongoing (HighSTEACS) [ 10 ]. However, wide ranges of incidence rates are reported, most likely as a consequence of an absent universal definition for UA [ 7 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, recent studies show substantial differences between UA and NSTEMI patients with regards to incidence and mortality. Moreover, the non-existence of myocardial injury in UA patients even suggests differences in pathophysiology [ 10 ]. Several studies showed higher rates of future MI and coronary revascularisation in UA patients compared with non UA/non ACS patients [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Japanese singlecentre study of 1233 patients found comparable late mortality and major adverse cardiac and cerebrovascular events between propensity matched ACS and stable CAD patients [9]. However, patients with MI have poorer prognosis than those with UA who are also included in ACS [21]. Despite the fact that patients who underwent CABG following unstable angina had better long-term survival than patients with NSTEMI, patients with unstable angina remain at high risk also after PCI when compared with stable CAD [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…[27] In our study, we have found that there were more patients diagnosed as NSTEMI among patients with fQRS than among patients without. In a recently published study by (Puelacher et al, [28], assessed the relative incidence and compared the characteristics and outcome of unstable angina (UA) and NSTEMI. Despite their similar clinical presentations and treatment strategies, Puelacher and his colleagues have found that all-cause mortality was significantly higher in patients with NSTEMI compared with UA patients despite of similar incidence of future non-fatal myocardial infarction was comparable between the two groups.…”
Section: Discussionmentioning
confidence: 99%